2012
DOI: 10.3892/ijmm.2012.1183
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profiles in spontaneously hypertensive rats induced by administration of enalapril and nifedipine

Abstract: Enalapril and nifedipine are used as antihypertensive drugs; however, the therapeutic target molecules regulated by enalapril and nifedipine have yet to be fully identified. The aim of this study was to identify novel target genes that are specifically regulated by enalapril and nifedipine in tissues from spontaneously hypertensive rats (SHR) using DNA microarray analysis. We found that administration of SHR with enalapril and nifedipine differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(33 reference statements)
1
6
0
1
Order By: Relevance
“…It cannot be ruled out that in the experimental conditions, enalapril upregulates coordinately expression of both NF-kB and IGF-IR (shown in our studies) since IGF-IR promoter contains NF-kB binding site (Ma et al 2006 ). Such a hypothesis seems to be reasonable since recently it was found that enalapril and nifedipine differentially regulate 33 genes involved in the pathogenesis of cardiovascular diseases (Lee et al 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…It cannot be ruled out that in the experimental conditions, enalapril upregulates coordinately expression of both NF-kB and IGF-IR (shown in our studies) since IGF-IR promoter contains NF-kB binding site (Ma et al 2006 ). Such a hypothesis seems to be reasonable since recently it was found that enalapril and nifedipine differentially regulate 33 genes involved in the pathogenesis of cardiovascular diseases (Lee et al 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…There are significant data showing that treatment with anti-hypertensive drugs leads to changes in gene expression in the kidneys and bladder tissue ( 4 , 5 ). Additionally, a recent study demonstrated that treatment with such drugs may also result in changes in gene expression directly in the heart, brain and liver tissues ( 6 ). The authors reported on differentially expressed genes following treatment with anti-hypertensive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Genes that are differentially expressed following treatment with anti-hypertensive drugs may be potential biomarkers and novel targets for the prevention of cardiovascular disease. Moreover, such genes may provide valuable information for the development of new anti-hypertensive therapy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…IL‐24 is secreted by both immune and nonimmune cells. Lee et al found that the expression of IL‐24 decreased in spontaneously hypertensive rats but increased after treatment with antihypertensive drugs . In addition, IL‐24 treatment attenuated the expression of vascular inflammation and hypertension‐related genes in mouse vascular smooth muscle cells, indicating that IL‐24 is a novel therapeutic target for hypertension.…”
mentioning
confidence: 99%